2018
DOI: 10.1093/cid/ciy152
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Release Syndrome Grade as a Predictive Marker for Infections in Patients With Relapsed or Refractory B-Cell Acute Lymphoblastic Leukemia Treated With Chimeric Antigen Receptor T Cells

Abstract: NCT01044069.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
330
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(351 citation statements)
references
References 32 publications
15
330
2
4
Order By: Relevance
“…In a study using multivariable modelling, CRS severity was the only significant risk factor for infection (Hill et al , ). Supporting this, another study using a different CD19 CAR‐T cell product also demonstrated an increase in infections, particularly bloodstream infections with severe CRS (Park et al , 2018b).…”
Section: Clinical Presentation Of Crsmentioning
confidence: 78%
“…In a study using multivariable modelling, CRS severity was the only significant risk factor for infection (Hill et al , ). Supporting this, another study using a different CD19 CAR‐T cell product also demonstrated an increase in infections, particularly bloodstream infections with severe CRS (Park et al , 2018b).…”
Section: Clinical Presentation Of Crsmentioning
confidence: 78%
“…Most infections are caused by bacteria typical for patients with hematologic malignancies undergoing chemotherapy and occur early after CAR‐T cell infusion, during periods of neutropenia, following the onset of CRS . The incidence of life‐threatening or fatal infections is low . In a study at our institution, patients with ALL, more prior antitumor treatment regimens, a higher CAR‐T cell dose, and more severe CRS were at increased risk of infection .…”
Section: Other Toxicities Of Cd19 Car‐t Cell Immunotherapymentioning
confidence: 96%
“…Patients receiving CAR‐T cell therapies may be at risk of infection due to underlying immune suppression, the effects of lymphodepletion, or the consequence of on‐target, off‐tumor toxicity resulting in B cell depletion in the case of CD19 CAR‐T cells. Most infections are caused by bacteria typical for patients with hematologic malignancies undergoing chemotherapy and occur early after CAR‐T cell infusion, during periods of neutropenia, following the onset of CRS . The incidence of life‐threatening or fatal infections is low .…”
Section: Other Toxicities Of Cd19 Car‐t Cell Immunotherapymentioning
confidence: 99%
“…Most treatment-related death was due to these two adverse events [27]. In addition, the persistence of in vivo CAR-T cells usually contributes to prolonged B cell aplasia [22,28,29], which can potentially lead to infectious complications [30,31].…”
Section: Introductionmentioning
confidence: 99%